Criminal Law Challenges For Digital Cooperatives In Cirebon: Upholding Dignified Justices In The Digital Age - Sukardi, Didi; Hamamah, Fatin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
This research aims to identify the criminal law challenges faced by cooperatives in Cirebon in maintaining dignified justice and to provide legal protection recommendations for cooperative members in the digital era. It examines how digital technology impacts the justice principles within cooperatives and highlights the gap between cooperative theory and criminal law practices, which often struggle to address the complexities of violations in digital cooperatives. The study offers novel insights by integrating criminal law analysis with digital cooperative management, focusing on technology misuse threats. Using a qualitative approach, this research employs literature review, normative juridical analysis, and case studies to explore criminal law applications in digital cooperatives. Findings reveal that digital-era cooperatives face significant risks, including data breaches, fraud, and technology misuse by administrators or members. The study underscores the urgency of regulatory updates and stricter criminal law enforcement to safeguard cooperative members' rights and uphold justice. Keywords: digital era; criminal law; dignified justices; cooperatives; technology misuse